Colombo : Exposure, Vulnerability, and Ability to Respond to Floods - Patankar, Archana (World Bank, Washington, DC, 2017)
This paper examines the exposure, vulnerability, and ability of households in Colombo, Sri Lanka, to respond to floods, and brings out significant policy implications. The study used detailed questionnaire-based surveys to obtain data on households, to understand the vulnerability and impacts of the severe floods of November 2010 and recurrent floods since then. Households that were selected for the surveys were located in and around flooding spots in the city. The study finds that the floods have imposed a significant burden on poor households. Poor and nonpoor households have suffered damages to the structure of their houses, household assets and appliances, and vehicles. With recurrent floods, they continue to bear the cost of damages as well as short-term measures to cope with floods. For poor families, these costs are borne through very limited resources and borrowing from informal sources, compared with the nonpoor who have more savings in financial form and greater access to formal sources of credit. Poor families tend to invest all their earnings in their home, furniture, and utensils, which suffer the most during floods. In addition, households suffer indirect impacts due to non-availability of transport, power, drinking water, food, and essential supplies. They also tend to lose workdays, which leads to loss of income and productivity. Many poor families have considered relocation to flood-free areas, but they lack the financial resources for the move. If the government offers such a scheme, many would be willing to take it up, if factors like job opportunities, clean surroundings, access to medical facilities, transportation, and good social networks are ensured in the new locations.